Abiotic factors influencing podophyllotoxin and yatein overproduction in Leptohyptis macrostachys cultivated in vitro. (December 2017) - Meira, Paloma R.; David, Juceni P.; de O. Ribeiro, Erika M.; Santana, José R.F.; Brandão, Hugo N.; de Oliveira, Lenaldo M.; David, Jorge M.; Medrado, Héctor H.; Pastore, José F.B.
Graphical abstract: Highlights: Overproduction of podophyllotoxin and yatein were carried obtained in in vitro Leptohyptis macrostachys cultures. PCA and HCA analysis of all experiment results indicated two PC are responsible for 100% data variance. Podophyllotoxin was on average higher BAP and NAA growth regulators and yatein in absence of NAA. Abstract: This work describes an in vitro propagation protocol for the large-scale cultivation of Leptohyptis macrostachys (Benth.) Harley & JFB Pastore and the influence of abiotic factors on podophyllotoxin and yatein production. The plant was established from seeds collected in Chapada Diamantina, BA, Brazil and submitted to different growth mediums and physical conditions. The podophyllotoxin and yatein contents were quantified by HPLC/DAD and with pure standards and these two lignans were present in all experiments. The lignan quantities were evaluated using the Sisvar Program, compared by Tukey's test and hierarchical cluster analysis and principal component analysis. In all experiments, podophyllotoxin and yatein were detected at different concentrations. The best protocol cultivar of L. macrostachys was established from seeds in MS ½ medium supplemented with 1.5% sucrose and 11.55 μM of gibberellic acid A3 (GA3 ) at 30 °C, which yielded the highest concentration of podophyllotoxin (5.831 mg g −1 ). These results are important findings for the production of podophyllotoxin from the tissue culture.